2018
DOI: 10.3389/fonc.2018.00590
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Autophagy in Cancer-Associated Fibroblasts Supports Chemotherapy of Pancreatic Cancer Cells

Abstract: In this study we evaluated the interaction of pancreatic cancer cells, cancer-associated fibroblasts, and distinct drugs such as α-cyano-4-hydroxycinnamate, metformin, and gemcitabine. We observed that α-cyano-4-hydroxycinnamate as monotherapy or in combination with metformin could significantly induce collagen I deposition within the stromal reaction. Subsequently, we demonstrated that cancer-associated fibroblasts impaired the anti-proliferation efficacy of α-cyano-4-hydroxycinnamate, metformin and gemcitabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…A short period of neutropenia may indicate a deficient dosage and a lack of lethality . Previous studies have shown that the matrix response produces a physical barrier to defend carcinoma cells from chemotherapy in solid tumors, and inhibiting autophagy in CAFs contributes to the effects of chemotherapy on pancreatic cancer . Stage II‐III GAC patients with the SMA low CD66b low phenotype might benefit from adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A short period of neutropenia may indicate a deficient dosage and a lack of lethality . Previous studies have shown that the matrix response produces a physical barrier to defend carcinoma cells from chemotherapy in solid tumors, and inhibiting autophagy in CAFs contributes to the effects of chemotherapy on pancreatic cancer . Stage II‐III GAC patients with the SMA low CD66b low phenotype might benefit from adjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs like metformin and gemcitabine are reported to induce autophagy. The combination of chemotherapeutic like α-cyano-4-hydroxycinnamate (CHC) alone and in combination with metformin is reported to hinder autophagic flux in CAFs and hampers tumor cell proliferation, irrespective of chemotherapeutic agents in in vitro and in syngeneic pancreatic cancer model [86].…”
Section: Cancer-associated Fibroblast (Cafs)mentioning
confidence: 99%
“…Moreover, blocking autophagy in CAFs could supports chemotherapy through proliferation inhibition in pancreatic, oral squamous cell carcinoma and pancreatic adenocarcinoma cancer cells [7375]. Radiation-induced rescue effect is closely related to radiation-induced bystander effect and describes the phenomenon that irradiated cells derive benefits from feedback signals released from bystander unirradiated cells, then alleviate the harmful radiobiological effects.…”
Section: Introductionmentioning
confidence: 99%